Association of dietary patterns with acne vulgaris severity among adolescents: A cross-sectional study. - Dr. R. Meenakshi; Kumari, Dr. S. Vasantha; Mogili, Dr. Prashanthi (Student’s Journal of Health Research Africa, 2025)
Background: Acne vulgaris is a prevalent dermatological disorder among adolescents, influenced not only by genetic and hormonal factors but also by lifestyle and dietary habits. Identifying modifiable risk factors, particularly dietary patterns, is essential to reducing disease burden and improving quality of life. Objectives: To assess the association between dietary patterns and the severity of acne vulgaris among adolescents. Methods: A cross-sectional study was conducted among 100 adolescents aged 13–19 years. Data regarding demographic characteristics, dietary patterns, and specific food consumption were collected using a pretested questionnaire. Acne severity was graded using the Global Acne Grading System (GAGS). Dietary intake was classified into traditional, mixed, and Western patterns. Statistical analysis was performed using the chi-square test, with p < 0.05 considered significant. Results: The study population comprised 42% males and 58% females, with a mean age of 16.2 ± 2.1 years. Acne severity was mild in 34%, moderate in 46%, and severe in 20% of participants. The Western dietary pattern was reported in 41% of adolescents and showed the highest prevalence of moderate (58.5%) and severe acne (29.3%). In contrast, the traditional dietary pattern was associated with a lower prevalence of severe acne (13.6%) (p = 0.002). Frequent intake of dairy products (>4 times/week) and sugary beverages (>3 times/week) significantly increased acne severity (p = 0.03 and p = 0.01, respectively). Conversely, higher consumption of fruits and vegetables (>5 servings/day) was associated with reduced severity (p = 0.04). Conclusion: Westernized dietary habits, particularly high consumption of dairy and sugary drinks, are significantly associated with greater acne severity among adolescents, while fruit- and vegetable-rich diets appear protective. Recommendations: Adolescents should be encouraged to adopt balanced dietary habits emphasizing fruits, vegetables, and whole foods while limiting high-glycemic, dairy, and processed foods.